Stabilność posturalna starszych kobiet przed i po dziesięciu tygodniach ćwiczeń metodą Pilates = Postural stability of elderly women before and after ten weeks of Pilates exercises - Pyskir, Małgorzata; Pyskir, Jerzy; Ratuszek-Sadowska, Dorota; Sebastian, Joanna; Bosek, Maciej; Hagner-Derengowska, Magdalena; Hagner, Wojciech (Journal of Education, Health and Sport, 2016)
Pyskir Małgorzata, Pyskir Jerzy, Ratuszek-Sadowska Dorota, Sebastian Joanna, Bosek Maciej, Hagner-Derengowska Magdalena, Hagner Wojciech. Stabilność posturalna starszych kobiet przed i po dziesięciu tygodniach ćwiczeń metodą Pilates = Postural stability of elderly women before and after ten weeks of Pilates exercises. Journal of Education, Health and Sport. 2016;6(12):243-258. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.198452 http://ojs.ukw.edu.pl/index.php/johs/article/view/4049 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 09.12.2016. Accepted: 09.12.2016. Stabilność posturalna starszych kobiet przed i po dziesięciu tygodniach ćwiczeń metodą Pilates Postural stability of elderly women before and after ten weeks of Pilates exercises Małgorzata Pyskir1, Jerzy Pyskir2, Dorota Ratuszek-Sadowska1, Joanna Sebastian1, Maciej Bosek2, Magdalena Hagner-Derengowska3, Wojciech Hagner1 Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Katedra i Zakład Biofizyki, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Bydgoska Szkoła Wyższa, Bydgoszcz Streszczenie Wstęp Jedną z charakterystycznych cech człowieka jest stabilna pionowa postawa ciała. Nieprawidłowe działanie systemu kontroli postawy (PCS) może powodować niekontrolowane upadki, co pogarsza kondycję fizyczną i ogranicza funkcje życiowe. Wykazano, że kontrola postawy u osób starszych jest utrudniona. Być może właściwie prowadzona rehabilitacja jest w stanie spowolnić ten proces. Cel Dotychczasowe badania pokazały pozytywny wpływ ćwiczeń Pilates na elastyczność tułowia i miednicy oraz równowagę dynamiczną. Celem niniejszej pracy było porównanie stabilności postawy starszych kobiet przed i po 10 tygodniach programu ćwiczeń metodą Pilates. Materiał i metody W badaniach wzięło udział 35 kobiet w wieku 55-67 lat. Wstępne badanie posturograficzne wykonano przed rozpoczęciem ćwiczeń. Następnie uczestniczki programu przez 10 tygodni wykonywały ćwiczenia metodą Pilates pod opieką wykwalifikowanego fizjoterapeuty. Po zakończonym programie powtórzono badanie posturograficzne. Wyniki Analizowano pole powierzchni oraz długość rejestrowanych statokinezjogramów. Dokonano także analizy dyfuzyjnej otrzymanych krzywych. Ponad 60% uczestniczek uzyskało lepsze rezultaty w po programie ćwiczeń. Osoby, które w drugim badaniu miały gorsze wyniki donosiły, że były w dniu badania przeziębione lub mocno zmęczone. Wnioski Pogorszenie stabilności postawy u osób starszych można minimalizować przez intensyfikację codziennej aktywności. Może jej pomóc wykonywanie ćwiczeń metodą Pilates. Badania posturograficzne stanowią dobre narzędzie do monitorowania pracy systemu kontroli postawy. Słowa kluczowe: stabilność posturalna, system kontroli postawy (PCS), Pilates Abstract Introduction One of characteristic of humans is upright standing. Incorrect operation of Postural Control System (PCS) can cause falls. It can lead to deterioration of physical condition and limitations of vital functions. It was shown that operation of PCS deteriorates with age. Perhaps this process can be slowed down using proper rehabilitation. Aim It was reported than Pilates method of exercise (PME) has positive effect on flexibility of trunk and pelvis and dynamic balance. The purpose of this paper is comparison of postural stability in the group and elderly women before and after 10 weeks of Pilates exercises. Materials and methods A total of 35 women of age 55 to 67 years were investigated. The preliminary posturographic test was performed before exercises. Over the next ten weeks women participated weekly in the Pilates exercises conducted by physiotherapist. At the end of the program the investigation was repeated. Results The sway area and the length of COP trajectory were determined twice. The diffusion analysis of COP trajectory was also performed. In the over 60% of participants the parameters after exercises were better than before program. Some women obtained worse result . However, they reported cold or tiredness in the day of second measurement. Conclusions The problem of postural stability deterioration of elderly people can be minimized by a more intense daily physical activity. The PME can help to maintain good work of PCS. The results can be monitored by posturographic tests. Key words: postural stability, PCS, Pilates method of exercise (PME)